Geometrische Maßtheorie: 12.6. bis 16.6.1973 - Hildebrandt, Stefan; Jäger, Willi; Steffen, Klaus (Tagungsbericht, 1973)
H. W. Alt, Münster; W. Alt, Münster; G. Bertellini, Pisa; R. Böhme, Göttingen; C. Gerhardt, Mainz; K. Goldhorn, Mainz; K. Gornik, Bonn; F. P. Harth, Bonn; S. Hildebrandt, Bonn; E. Hölder, Mainz; W. Jäger, Münster; H. Jarausch, Münster; H. Kaul, Bonn; H. Schmidt, Münster; E. Sperner, Bonn; K. Steffen, Bonn; F. Tomi, Münster; H. Wente, Toledo
Keywords: Konferenzschrift